PERISTILAHAN BUDAYA DALAM RITUAL TRADISI BOBOREN PADA MASYARAKAT DAYAK JANGKANG DI KECAMATAN JANGKANG, KABUPATEN SANGGAU - Yani, Marisa Fransiska; Syahrani, Agus; Muzammil, Ahmad Rabi’ul (Universitas Tanjungpura, 2024)
This research aims to classify data obtained from the field, carry out an inventory of the data in the form of terminology, lexical meaning and cultural meaning, and produce a supplementary form of Indonesian language learning text based on Cultural Terminology in the Rituals of the Boboren Tradition in the Jangkang Dayak Community in Jangkang District, Sanggau Regency. The method used in this research is a descriptive method in qualitative form. The data sources in this research are people or community leaders who really understand the boboren tradition. The informants in this research were Emelia Poni (Semombat Village) aged 45 years, Jimpui (Semombat Village) aged 54 years, Cristian Mara (Dusun Rosak) aged 57 years. Data collection techniques are interview, recording and documentation techniques. Data validity testing techniques include techniques to increase persistence, triangulation, reference skills, and peer examination. This research produced 112 data on cultural terminology in the rituals of the boboren tradition in the Jangkang Dayak Community in Jangkang District, Sanggau Regency with details of 19 terms in the form of monomorphemic terms and 41 data in the form of polymorphemic terms. There are 52 data on lexical meaning and 7 data on cultural meaning in boboren ritual terminology, 13 data on process terminology, 34 data on tool and material terminology, and 6 data on perpetrator terminology. This research also produces an Indonesian language learning text based on Cultural Terminology in the Rituals of the Boboren Tradition in the Jangkang Dayak Community in Jangkang District, Sanggau Regency.